Segmentation of retail customers based on cluster analysis in building successful CRM. (2016) - Gupta, Gaurav; Aggarwal, Himanshu; Rani, Rinkle
Direct marketers uses data mining technique called segmentation based on cluster analysis to target a subset of their customers for improving their profits. As the world is growing more and more competitive, the customer need and experience is becoming more important to the businesses. CRM based on data mining is a comprehensive strategy and a process of acquiring, retaining, and partnering with selective customers to create superior value for the business by using customer knowledge. The objective of the paper is to segment the relevant customers through cluster analysis that may be helpful to the marketers in increasing their profit, sales and building long-term relationships with them. Segmentation of the customers can be achieved through cluster analysis. The findings in the paper may help the retailers to focus those segments of customers that increase their business, sales and profit and also aid in customer build ups and maintaining long-term relationships.